Macroporous Silica with Thick Framework for Steam‐Stable and High‐Performance Poly(ethyleneimine)/Silica CO2 Adsorbent. Issue 11 (16th May 2017) - Min, Kyungmin; Choi, Woosung; Choi, Minkee
Abstract: Poly(ethyleneimine) (PEI)/silica has been widely studied as a solid adsorbent for post‐combustion CO2 capture. In this work, a highly macroporous silica (MacS), synthesized by secondary sintering of fumed silica, is compared with various mesoporous silicas with different pore structures as a support for PEI. The silicas with large pore diameter and volume enabled high CO2 adsorption kinetics and capacity, because pore occlusion by the supported PEI was minimized. The steam stability of the silica structures increased with the silica wall thickness owing to suppressed framework ripening. The silicas with low steam stability showed rapid leaching of PEI, which indicated that the PEI squeezed out of the collapsed silica pores leached more readily. Consequently, MacS that had an extra‐large pore volume (1.80 cm 3  g −1 ) and pore diameter (56.0 nm), and a thick wall (>10 nm), showed the most promising CO2 adsorption kinetics and capacity as well as steam stability. Abstract : Steam‐stable CO2 adsorbents : Silica supports—a highly macroporous silica (MacS) and three mesoporous silicas (MCM‐41, SBA‐15, and mesocellular foam (MCF))—are compared as a support for 50 wt % poly(ethyleneimine) (PEI). MacS, which has an extra‐large pore diameter and volume, and a thick wall, exhibits the best CO2 adsorption capacity and kinetics as well as steam stability.